The Capability Approach and Sociological Conceptions of Human Agency: An Empirical Assessment on the Basis of an Analysis of Activation Policies - Stephan Dahmen (Social Work and Society)
From the mid-nineties on, European welfare states are facing formidable pressures. As a response to these pressures, a strong international reform agenda has found support around the ideas that benefit recipients have to be"activated" in order to find Jobs. Such approaches conceive the aim of welfare states to strengthen Social Policy as a productive factor and to provide the"right" incentives and compulsion (carrots and sticks) in order to control and design behaviour of persons (van Berkel, 2010; Handler, 2004). On an ideological level, these developments correspond to a shift from previously contested assumptions about human motivation, choice, agency and human responsibility of beneficaries of the welfare state. In Critical Social Policy research, a discussion has emerged around the models of human motivation and agency that have been influential in policy design (see e.g. Le Grand, 2003; Deacon, 2005; White, 2013). The article argues that conceptions of human agency have important political implications when it comes to debates about individual responsibility. This may lead to so called"autonomy gaps" (Anderson, 2009), or to situations in which welfare beneficaries perceive the instituionalized imperative to autonomy as an injunction. The article confronts the capability approach (C.A.) to different competing sociological conceptions of human agency. On the basis of an empirical study of the construction of welfare subjects through activation policies, the article points to some shortcomings of the C.A. especially for the analysis of the micro-workings of power in post-disciplinary societies, in which the exercise of power does not so much consist of imposing direct constraints upon citizens as of"governing trough freedom". For this reason, the article argues that Sen's realization-based approach needs to be supplemented by concepts which allow accounting for the social mediatedness of individual identities and for the social construction of subjectivity within different social contexts.